Folliculin Controls the Intracellular Survival and Trans-Epithelial Passage of Neisseria gonorrhoeae - Yang, Tao; Heydarian, Motaharehsadat; Kozjak-Pavlovic, Vera; Urban, Manuela; Harbottle, Richard P.; Rudel, Thomas (Frontiers in Cellular and Infection Microbiology, 2020)
Neisseria gonorrhoeae, a Gram-negative obligate human pathogenic bacterium, infects human epithelial cells and causes sexually transmitted diseases. Emerging multi-antibiotic resistant gonococci and increasing numbers of infections complicate the treatment of infected patients. Here, we used an shRNA library screen and next-generation sequencing to identify factors involved in epithelial cell infection. Folliculin (FLCN), a 64 kDa protein with a tumor repressor function was identified as a novel host factor important for N. gonorrhoeae survival after uptake. We further determined that FLCN did not affect N. gonorrhoeae adherence and invasion but was essential for its survival in the cells by modulating autophagy. In addition, FLCN was also required to maintain cell to cell contacts in the epithelial layer. In an infection model with polarized cells, FLCN inhibited the polarized localization of E-cadherin and the transcytosis of gonococci across polarized epithelial cells. In conclusion, we demonstrate here the connection between FLCN and bacterial infection and in particular the role of FLCN in the intracellular survival and transcytosis of gonococci across polarized epithelial cell layers.